Aspects of one-dimensional channel gas dynamics with friction and heat transfer - Федоров, М.Ю. (Proceedings of National Aviation University (archive), 2006)
In the paper the second form of analytical solution is obtained for the problem of one-dimensional steady compressible flow of perfect gas with constant heat flux and friction in the constant-area duct. The possibility is analyzed for obtaining analytical solutions under other boundary conditions. The future studies and application of the analytical solution in engineering practice is discussed.